Analisis Peran Interactivity, Informativeness dan Trendiness pada Akun Instagram Merek 'Somethinc' terhadap Customer Brand Engagement dan Brand Loyalty - Putri, Shafira Maritza; Ihsan, Mochamad Chairul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Social media such as Instagram is increasingly popular as a marketing platform, including in the cosmetics industry. Somethinc is one of the local cosmetic brands that utilize Instagram as a marketing platform with content that is interactive, informative, and taps into current trends. This quantitative research aims to determine the influence of the role of interactivity, informativeness, and trendiness of social media marketing activities that has been done by ‘Somethinc’ brand on customer brand engagement and brand loyalty. In addition, this study also explores the role of customer brand engagement as a mediator in the relationship between interactivity, informativeness, and trendiness to brand loyalty. Data was collected through online questionnaires distribution with a total 167 respondents. All respondents are active Instagram users who followed @somethincofficial Instagram account and have purchased ‘Somethinc’ brand products in the last 3 months. The data that has been collected is analyzed using SEM-PLS method. The results of this study shows that there is a positive relationship from the role of interactivity, informativeness, and trendiness to customer brand engagement. Furthermore, customer brand engagement also has a positive relationship with the formation of brand loyalty. It can also be seen that customer brand engagement mediates the positive relationship between interactivity, informativeness, and trendiness with brand loyalty.